Effect of Statins on Serum level of hs-CRP and CRP in Patients with Cardiovascular Diseases: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Tahmineh Kandelouei; Mitra Abbasifard; Danyal Imani; Saeed Aslani; Bahman Razi; Mahdieh Fasihi; Sajad Shafiekhani; Keyhan Mohammadi; Tannaz Jamialahmadi; Željko Reiner; Amirhossein Sahebkar (Mediators of Inflammation)
Background. Several studies have reported that statins have anti-inflammatory effects. Nevertheless, results of clinical trials concerning the effect of statins on the levels of C-reactive protein (CRP) and high-sensitivity CRP (hs-CRP) have been inconsistent. Therefore, we performed a systematic review and meta-analysis of randomized clinical trials (RCTs) evaluating the effect of statins on CRP and hs-CRP levels in patients with cardiovascular diseases (CVDs). Methods. Literature search of the major databases was performed to find eligible RCTs assessing the effect of statins on serum levels of CRP and hs-CRP from the inception until the last week of April 2021. The effect sizes were determined for weighted mean difference (WMD) and 95% confidence intervals (CI). Results. 26 studies were identified (3010 patients and 2968 controls) for hs-CRP and 20 studies (3026 patients and 2968 controls) for CRP. Statins reduced the serum levels of hs-CRP (WMD=−0.97 mg/L; 95% CI: -1.26 to -0.68 mg/L; P<0.001) and CRP (WMD=−3.05 mg/L; 95% CI: -4.86 to -1.25 mg/L; P<0.001) in patients with CVDs. Statins decreased the serum levels of hs-CRP in patients receiving both high-intensity and moderate/low-intensity treatments with these drugs. In addition, the duration of treatment longer than 10 weeks decreased hs-CRP levels. Only high-intensity statin treatment could marginally decrease serum levels of CRP in CVDs patients. Conclusions. This meta-analysis showed the efficacy of statins to reduce the concentrations of CRP and hs-CRP in patients with different types of CVDs.